Analisis Faktor-Faktor Yang Memotivasi Mahasiswa Dalam Berwirausaha (Studi Pada Mahasiswa FEB Universitas Muhammadiyah Metro) - Ardani, Tri Ayu; Suwarto, Suwarto (Universitas Muhammadiyah Metro, 2022)
Ardani, Tri Ayu. 2021. “Analysis of Factors That Motivate Students in Entrepreneurship (Study on FEB Students, University of Muhammadiyah Metro)”. Thesis. Faculty of Economics and Business, Management Studies Program, University of Muhammadiyah Metro. Supervisor (I) Dr. H. Febriyanto, SE, MM Supervisor (II) Ardiyansyah Japlani, SE, M.BA., AWM. Keywords: Success, Work Motivation, Need for Achievement, Instrumentation Readiness, and Interest in Entrepreneurship. This researcher aims to analyze the motivational factors of students in entrepreneurship. This type of research is a quantitative study with a population of 222 students who are active at the University of Muhammadiyah Metro Batch 2017, only 143 samples used are in accordance with predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis is multiple linear regression analysis and tested using the statistical packages for the social science (SPSS) version 20 program. Based on the results of statistical tests, it shows that success, motivation at work, need for achievement and readiness of instrumentation have a positive and significant influence on entrepreneurial interest in FEB students, Muhammadiyah Metro University.